PERAN KEPALA SEKOLAH DALAM PENERAPAN KURIKULUM KMA NOMOR 183 DAN NOMOR 184 TAHUN 2019 DI MADRASAH ALIYAH AL-ANWAR PACULGOWANG DIWEK JOMBANG - Roziqin, Muhamad Khoirur; Zainal Abidin, Moch Rifqi (Universitas KH. A. Wahab Hasbullah, 2021)
The importance of the role of the principal in implementing the KMA curriculum Number 183 and Number 184 of 2019, so that teaching and learning activities in schools are activities that must be endeavored as much as possible. The purpose of this study was to find out about the role of school principals in implementing the KMA curriculum Number 183 and Number 184 of 2019 at Madrasah Aliyah Al-Anwar Paculgowang Diwek Jombang as well as supporting and inhibiting factors in implementing the KMA curriculum Number 183 and Number 184 2019. This research is a field research, meaning that this research takes data objectively, using qualitative methods. The results of this study, principals act as mentors, managers, supervisors, and facilitators. The supporting factors are internal and internal factors. Internal factors include that the school has adequate human resources, this curriculum is in accordance with the needs of the community, the principal is assisted by the deputy head of the curriculum. The external factor is that this curriculum has the support of parents and guardians of students, the school is in a supportive area, meaning that it is in the area of ​​a boarding school, on the other hand students have received religious subjects outside of school, the principal is helped by the presence of qualified teachers. the inhibiting factors are that there are some children who are slow in understanding the subject, the learning media is not evenly distributed in the classroom.